Dural and arachnoid membraneous protection of the abducens nerve at the petroclival region - Ozveren, MF; Uchida, K; Tekdemir, I; Cobanoglu, B; Akdemir, I; Kawase, T; Deda, H (Thieme Medical Publ Inc, 2002)
The goal of this study was to determine the membranous protection of the abducens nerve in the petroclival region. The petroclival portion of the abducens nerve was studied in ten dissections from five cadaveric head specimens. One of the heads was used for histological sections. Four heads were injected with colored latex for microsurgical dissections. The histological sections were prepared from petroclival dura mater, embedded in paraffin blocks, stained, sectioned in the axial, coronal, and sagittal planes, and evaluated by light microscopy. The abducens nerve was covered by a dural sleeve and arachnoidal membrane during its course within the petroclival area. Following the petrous apex, the abducens nerve was fixed by a sympathetic plexus and connective tissue extensions to the lateral wall of the cavernous segment of the internal carotid artery and to the medial wall of Meckel's cave. Fibrous trabeculations inside the venous space were attached to the dural sleeve. The lateral clival artery accompanied the dural sleeve of the abducens nerve and supplied the petroclival dura mater. The arterioles accompanying the abducens nerve through the subarachnoid space supplied the nerve within the dural sleeve. The arachnoid membrane covered the abducens nerve within the dural sleeve to the petrous apex, and arachnoid granulations found on the dural sleeve protruded into the venous space. The extension of the arachnoid membrane to the petrous apex and the presence of arachnoid granulations on the dural sleeve suggest that the subarachnoid space continues in the dural sleeve.
Keywords: abducens nerve; arachnoid membrane; dural sleeve; petroclival region; subarachnoid space